PENGEMBANGAN WISATA BUDAYA KABUPATEN BENGKALIS TAHUN 2018 - Anggara Sattya Pratama; Raja Muhammad Amin (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2020)
The wealth of natural resources and cultural diversity possessed by Bengkalis Regency is a great potential that needs to be optimized by the Bengkalis Regency Government and related parties in order to develop and manage that potential. The potential of natural beauty and cultural diversity is a major force in developing the tourism sector in Bengkalis Regency, such as beach tourism, lake tourism and cultural tourism as well as other tourism. This study aims to determine the Cultural Tourism Development of Bengkalis Regency in 2018. Data collection techniques used were documentation and observation interview techniques. The formulation of the problem in this study is How is the development of cultural tourism in Bengkalis Regency in 2018? and inhibiting factors in the development of cultural tourism in Bengkalis Regency in 2018?Based on the results of research and discussion, it can be concluded that the development of Bengkalis Regency's cultural tourism in 2018 in the form of Promotion, Improvement of Facilities and Infrastructure, Maintenance of Tourism Objects, Human Resources Training, and Incorporating Cultural Tourism Areas Become Icons of Bengkalis Regency. On the other hand it is also known that the development of cultural tourism is also included in the Riau 2020 vision. While the obstacles in Riau 2020 in Bengkalis Regency are inadequate budget for all cultural tourism in Bengkalis district and inadequate facilities and infrastructure contained in cultural tourism in the district Bengkalis. Keywords: Cultural Development and Tourism